Long-term Relationships between Carbon Sequestration, Hydrology, and Tephra Disturbance in a Northern Peatland (Kamchatka Peninsula, Russia) - Tilotta, Kristen Marie (2016)
Northern peatlands are one of the most important carbon reservoirs, storing one-third to one-half of the world’s soil carbon pool and thus changes in their carbon balance have the potential to cause a positive feedback to climate change. While recent studies have made progress in understanding the climatic controls on the global carbon cycle, few have studied the important interaction between landscape disturbance (via volcanic eruptions), carbon accumulation, and peatland hydrology. Kamchatka Peninsula in the Russian Far East provides a unique opportunity to study long-term peatland hydrology and carbon accumulation with respect to the role of disturbance, as the area has been subjected to repeated landscape disturbance by tephra deposition over the last 10,000 years. In this study, I use a 10,000-year-old peatland record from Krutoberegovo, Kamchatka Peninsula (Russian Far East) to examine the interaction between carbon accumulation, peat surface wetness, and landscape disturbance in the form of peat surface burial by volcanic ash (tephra). I specifically ask whether tephra deposition affected the hydrological regime of the peatland, its nutrient status, and its ability to store carbon. To answer this question, I use a suite of palaeoecological and geochemical analyses as follows. First, I use 16 AMS 14C age measurements to create an absolute timescale for peatland development. Second, I use the peatland chronostratigraphy and measurements of peat carbon content to reconstruct the long-term carbon accumulation rates (LORCA). Third, I employ testate amoeba (TA) as a hydrological proxy to reconstruct peat surface wetness over time. Fourth, I reconstruct the nutrient status of the peatland by comparing the carbon to nitrogen ratios (C/N), where higher nitrogen values and lower carbon values are indicative of more nutrient-rich environments and vice versa. My results show that the Krutoberegovo peatland experienced thirty-four different tephra deposition events during the last 10,000 years, of which nine were considered major regional markers, based on their thickness, unique geochemical signatures, and area of dispersal. The carbon sequestration potential of the Krutoberegovo peatland measured as long-term apparent rates of carbon accumulation (LORCA) shows a wide variability over the course of the Holocene ranging from 74.5 g C m-2 yr-1 to 7.91 g C m-2 yr-1, with a substantial decrease in accumulation rates during periods of high tephra loading. Although the mechanisms responsible for this process remain unclear, I hypothesize that changes in carbon sequestration following tephra loading of peat surface could be mediated by changes in microbial activity and wetland vegetation cover. High-resolution analysis of testate amoebae (TA) communities over the course of the Holocene shows a high degree of variability with frequent shifts in taxa dominance. The statistical analysis of testate amoeba taxa in relation to tephra-related environmental variables (total ash content and major eruptions) shows that tephra deposition explains to a large degree the shifts in TA communities. Total ash content explains 77.3% of the taxa variability, while major volcanic eruptions as discrete events explain 6.3%. However, when TA communities are grouped according to their hydrological affinities, tephra deposition does not seem to affect any particular hydrological group suggesting that tephra disturbance does not play a role in peatland hydrology. Analysis of carbon and nitrogen chemistry of the Krutoberegovo peat profile suggest that tephra loading of the peat surface induced a net loss of both carbon and nitrogen. The C/N ratios – a measure of nutrient availability in peatland ecosystems – show a variable but overall increasing trend, which may be related to an autogenic replacement of nutrient rich with nutrient poor wetland plant communities. However, periods with lower or decreasing C/N ratios seem to be associated with high tephra loading, suggesting that tephra deposition may have also played a role.